Analisis Campur Kode Bahasa Indonesia dan Bahasa Kutai di Kalangan Pedagang Pasar Gerbang Raja Mangkurawang Kecamatan Tenggarong - Oktavia, Rika; Setyawati, Meita; Elyana, Kukuh (Universitas Mulawarman, 2018)
This study aims to describe the form of code mixing between Indonesia and Kutai languages as well as the factors behind the occurred among traders at Pasar Gerbang Raja Mangkurawang, Tenggarong district. The analysis method used in this study is the contextual method. This research is a qualitative research, where the research that produces descriptive data in the form of written words. The data collection techniques used werw listening, recording and interviewing techniques. Based on the data analysis, it was found that the form of code mixing included the insertion of elements in the form of 28 words, 2 phrases and 1 clause. The background for the occurrence of code mixing is due to two factors, namely the speaker factor and the language factor. Speakers factor that causes code mixing, due to relaxedness and habits in language. Meanwhile, the linguistic factor is because speakers consider words from regional languages more refined.This study aims to describe the form of code mixing between Indonesia and Kutai languages as well as the factors behind the occurred among traders at Pasar Gerbang Raja Mangkurawang, Tenggarong district. The analysis method used in this study is the contextual method. This research is a qualitative research, where the research that produces descriptive data in the form of written words. The data collection techniques used werw listening, recording and interviewing techniques. Based on the data analysis, it was found that the form of code mixing included the insertion of elements in the form of 28 words, 2 phrases and 1 clause. The background for the occurrence of code mixing is due to two factors, namely the speaker factor and the language factor. Speakers factor that causes code mixing, due to relaxedness and habits in language. Meanwhile, the linguistic factor is because speakers consider words from regional languages more refined.